STUDI PERILAKU PETANI DALAM MENGHADAPI RISIKO DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA USAHATANI KUBIS DI KABUPATEN LAMPUNG BARAT - Prasmatiwi, Fembriarti Erry (Lampung University)
This research aimed at studying (1) cabbage farmersâ behaviour in facing risk, (2) factors determining risk decision on cabbage farming in West Lampung District. The research was located in the central production of cabbage farming at Sekincau and Balik BukitÂ subdistrict. There are 71 farmers selected using simple random sampling method. Data has collected in September â October 2005 and analysed by logit method.Â About 71% of farmers have risk neutral behavior and the rest (29%) have risk preferring behavior. Determining factors of the farmersâ behaviour were farming experience, income, and land tenure. To develop cabbage farming and to increase the income, farmers are suggested to change their behaviour to face of preferring risk. Farming extension should be conducted to give market information and to empower farmersâ resources to makeÂ farmers dare to allocate optimum production factors to achieve maximum profit.